On sex hormones in infertiled men The effect of ghrelin - Hamed Ali Hamed; Nazar Ahmed Naji; Muhammed Hammad Jasim (Tikrit Journal of Pure Science)
The present study was designed to evaluate the effect of ghrelin on sex hormones, follicle stimulating hormones, luteinizing hormones, Testosterone, and prolactin in infertiled men. Abnormal spermatogenesis is often associated with altered serum gonadotropins and testosterone. follicle stimulating hormones, luteinizing hormones, and testosterone levels They were estimated in 50 infertiled men. Results showed statistically significant increase (p< 0.05) in the mean of ghrelin, follicle stimulating hormones, luteinizing hormones, Thyroid stimulating hormones, Prolactin, fasting blood sugar , Triglyceride, High density lipoprotein, Very low density lipoprotein, in all the studied infertiled males patients when compared with the fertiled control (n=20). In addition there was no significant differences in the levels of testosterone , Cholesterol ,and Low density Lipoprotein, between the infertiled and fertiled men.